Aging and Adult Development Consideration for Physicians, Speech Pathologists, and Audiologists Regarding Communication and Communication Disorders - Beasley, Daniel S (Journal of All India Institute of Speech and Hearing)
In the United States of America in recent years, gerontology and geriatrics have received increased attention relative to the social and medical implications related to aging. The comments and data presented in the paper will be limited to information which is available regarding the area of geriatrics and geronto- logy in the United States, primarily because this type of information was not available to the author as it pertains to the country of India. It is the author’s belief, however, that the information to be presented below is basic to any popu- lation. Although the specific numbers may vary significantly and perhaps in some cases not so significantly from country to country, nevertheless the basic similarities between India and the U.S.A. in this area are probably much greater than their differences. Further, much of the details to be presented can be found in greater detail in the book, Aging: Communication Processes and Disorders, edited by D.S. Beasley and G.A. Davis (1980) (see references).